Clinical profile of simultaneous bilateral optic neuritis in adults - de la Cruz, J (BMJ Group, 2006)
AIM: To establish the clinical profile of simultaneous bilateral optic neuritis in adults, the efficacy of steroid therapy, extent of visual recovery, and neurological outcome. METHODS: The authors performed a retrospective review of records of patients referred to a neuro‐ophthalmology service with acute bilateral optic neuritis from 2000–4. Exclusion criteria included previous multiple sclerosis or myelopathy, known systemic disorders or medications associated with optic neuropathy, uveitis, or neoplasm. Patients received intravenous methylprednisolone followed by oral prednisone. Visual acuity (logMAR conversion), mean deviation (dB) for visual fields, percentage of Ishihara plates seen, ophthalmoscopy, and neurological evaluation were recorded at baseline and at 6 months or 12 months. Owing to strong correlation for visual loss between eyes, the results for the worse eye in each patient were analysed. RESULTS: 11 men and four women, with an age range of 18–64 years, had bilateral decreased vision, 12 with pain on eye movement. Except for one patient, no aetiology was found. All patients had normal neurological evaluations, average visual acuity 1.71 (SD 0.55), colour vision 2.7% (SD 9.9%), and mean deviation −25.35 dB (SD −7.95 dB). Both optic nerves showed abnormal signal on magnetic resonance imaging. 14 patients improved and their last average visual acuity, colour vision, and mean deviation were 0.36 (SD 0.54), 69% (SD 46%), and −7.05 dB (SD 8.40 dB), respectively. No patient developed a neurological problem during the follow up with a mean of 11 months. CONCLUSION: Idiopathic acute bilateral optic neuritis without myelopathy occasionally occurs in adults. Vision recovers with corticosteroid therapy and during the first year neurological dysfunction will frequently not occur.